2011
DOI: 10.1200/jco.2010.30.9880
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Receptor Protein Expression in Tumor Tissue and Prostate Cancer Progression

Abstract: PurposeData suggest that circulating 25-hydroxyvitamin D [25(OH)D] interacts with the vitamin D receptor (VDR) to decrease proliferation and increase apoptosis for some malignancies, although evidence for prostate cancer is less clear. How VDR expression in tumor tissue may influence prostate cancer progression has not been evaluated in large studies.Patients and MethodsWe examined protein expression of VDR in tumor tissue among 841 patients with prostate cancer in relation to risk of lethal prostate cancer wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
122
2
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 131 publications
(134 citation statements)
references
References 42 publications
5
122
2
5
Order By: Relevance
“…SOX9 IHC and ERG fusion status in PCa tissue microarrays. IHC was performed on tissue microarrays (TMAs) created from prostatectomy samples among men with prostate cancer in the Physicians' Health and Health Professionals Follow-up Studies tumor cohort as described in detail in 2 recent publications (42,48). IHC was performed on 5-micron sections of 6 TMAs using the SOX9 antibody as described above.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SOX9 IHC and ERG fusion status in PCa tissue microarrays. IHC was performed on tissue microarrays (TMAs) created from prostatectomy samples among men with prostate cancer in the Physicians' Health and Health Professionals Follow-up Studies tumor cohort as described in detail in 2 recent publications (42,48). IHC was performed on 5-micron sections of 6 TMAs using the SOX9 antibody as described above.…”
Section: Methodsmentioning
confidence: 99%
“…To determine whether SOX9 protein expression also correlated with TMPRSS2:ERG fusion, we carried out SOX9 immunohistochemical (IHC) assessment on a primary PCa tissue microarray from the Physicians' Health and Health Professionals Follow-up Studies, which had been assessed previously for TMPRS-S2:ERG fusion by FISH and IHC (42,43). Each tumor was scored based on staining intensity and fraction of cells that were positive (SOX9 addscore; representative SOX9-positive and -negative staining is shown in Supplemental Figure 1B).…”
Section: Figurementioning
confidence: 99%
“…It had previously been suggested that apoptosis mechanisms were important for the transformation of Barrett's esophagus into adenocarcinoma and that expression of VDR in the esophagus was important in regulating apoptosis (70). It has further been shown that high expression of VDR can impact disease progression and overall survival of prostate, colon, and breast cancers (65,67,71). In a very small study by…”
Section: Vdr and Other Vitamin D-related Genetic Factorsmentioning
confidence: 99%
“…Por exemplo, experimentos in vitro mostram os efeitos do calcitriol na inibição da angiogênese (redução de interleucina-8, fator induzido por hipóxia α-1 e fator de crescimento endotelial vascular) e proliferação (redução da matriz metaloproteinase-9 e ativador do plasminogênio, aumento de p21 e p27) em linhagens de células neoplásicas de mama, próstata e colo. [50][51][52][53] Em linha com os efeitos descritos, pacientes com tumores de próstata ou mama que possuem uma maior expressão do receptor para vitamina D (VDR) apresentam melhor sobrevida. [54][55][56] Embora estudos epidemiológicos apontem para uma relação entre deficiência de vitamina D e aumento da incidência de câncer, e estudos em animais e com cultivo celular reforcem essa relação, dados obtidos a partir de estudos clínicos são inconsistentes.…”
Section: Câncerunclassified